1999
DOI: 10.1111/j.1749-6632.1999.tb08724.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cyclooxygenase‐2 Expression: An Approach to Preventing Head and Neck Cancer

Abstract: Cyclooxygenase (COX) catalyzes the formation of prostaglandins (PG) from arachidonic acid. A large body of evidence has accumulated to suggest that COX-2, the inducible form of COX, is important in carcinogenesis. In this study, we determined whether (1) COX-2 was overexpressed in squamous cell carcinoma of the head and neck (HNSCC) and whether (2) retinoids, a class of chemopreventive agents, blocked epidermal growth factor (EGF)-mediated activation of COX-2 expression. Levels of COX-2 mRNA were determined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 23 publications
(34 reference statements)
4
57
0
Order By: Relevance
“…72 Indeed, our group has demonstrated that COX-2 is upregulated in oral carcinogenesis, in keeping with findings from others. 60,73 Thus, COX-2 was not expressed in normal oral mucosa, to some extent in dysplastic oral mucosa and in most specimens of oral carcinoma. Also, COX-2 was exclusively upregulated in oral premalignant lesions that were DNA aneuploid.…”
Section: Chemopreventive Strategy In Oral Premalignanciesmentioning
confidence: 96%
“…72 Indeed, our group has demonstrated that COX-2 is upregulated in oral carcinogenesis, in keeping with findings from others. 60,73 Thus, COX-2 was not expressed in normal oral mucosa, to some extent in dysplastic oral mucosa and in most specimens of oral carcinoma. Also, COX-2 was exclusively upregulated in oral premalignant lesions that were DNA aneuploid.…”
Section: Chemopreventive Strategy In Oral Premalignanciesmentioning
confidence: 96%
“…Activation of EGFR has been shown to induce increased COX-2 expression in various normal and tumor cell lines, including HNSCC cell lines (46)(47)(48)(49)(50)(51)(52)(53)(54). Both transforming growth factor-a and epidermal growth factor, ligands of EGFR, were found to induce COX-2 expression (46 -50).…”
Section: Chemoprevention For Hncmentioning
confidence: 99%
“…COX-2 is also overexpressed in transformed cells and in tumors (Dannenberg et al, 2001). Although chemopreventive strategies have focused on inhibitors of COX enzyme activity, the mechanism of COX-2 inhibition with anticancer activity is still well understood (Mestre et al, 1999). Moreover, selective COX-2 inhibitors have been found to prevent the formation of intestinal and skin tumors in experimental animals (Pentland et al, 1999).…”
Section: Introductionmentioning
confidence: 99%